2021
DOI: 10.1177/00207314211007100
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Implemented Macroeconomic Policy Responses and Multilateral Collaboration Strategies for Economic Recovery After a Crisis: A Rapid Scoping Review

Abstract: To promote postpandemic recovery, many countries have adopted economic packages that include fiscal, monetary, and financial policy measures; however, the effects of these policies may not be known for several years or more. There is an opportunity for decision makers to learn from past policies that facilitated recovery from other disease outbreaks, crises, and natural disasters that have had a devastating effect on economies around the world. To support the development of the United Nations Research Roadmap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(24 reference statements)
0
4
0
Order By: Relevance
“… 20 - 23 , 25 , 36 First, the positive impacts on fellows’ employment transitions into careers in sectors beyond the traditional academic setting may be attributed in part to the program’s emphasis on (1) enriched core competency and professional development, intended to develop skillsets to achieve success beyond an academic environment 16 , 24 ; (2) the dual mentorship from a health system leader within the organization and an academic at a Canadian university; and (3) a network of colleagues that span the country, currently comprised of 202 HSI fellows and alumni and their respective health system and academic supervisors, with a shared commitment to and expertise in evidence-informed health system improvement. 37 This cohort and the network within has sparked multiple collaborations across fellows and mentors, including research studies, teams, and articles, 38 - 42 a Network of Scholars program in Nova Scotia to advance LHSs, 9 , 43 and leadership of the CIHR National Cohort Training Program. 44 Second, similar to other training programs intended to provide experiential learning opportunities and diversify trainees’ potential career paths, 45 a halo effect of the HSI Fellowship program’s emphasis on experiential learning likely augmented the fellows’ awareness of employment positions and sectors beyond academia through exposure to other career pathways in their networks and embedded environment.…”
Section: Discussionmentioning
confidence: 99%
“… 20 - 23 , 25 , 36 First, the positive impacts on fellows’ employment transitions into careers in sectors beyond the traditional academic setting may be attributed in part to the program’s emphasis on (1) enriched core competency and professional development, intended to develop skillsets to achieve success beyond an academic environment 16 , 24 ; (2) the dual mentorship from a health system leader within the organization and an academic at a Canadian university; and (3) a network of colleagues that span the country, currently comprised of 202 HSI fellows and alumni and their respective health system and academic supervisors, with a shared commitment to and expertise in evidence-informed health system improvement. 37 This cohort and the network within has sparked multiple collaborations across fellows and mentors, including research studies, teams, and articles, 38 - 42 a Network of Scholars program in Nova Scotia to advance LHSs, 9 , 43 and leadership of the CIHR National Cohort Training Program. 44 Second, similar to other training programs intended to provide experiential learning opportunities and diversify trainees’ potential career paths, 45 a halo effect of the HSI Fellowship program’s emphasis on experiential learning likely augmented the fellows’ awareness of employment positions and sectors beyond academia through exposure to other career pathways in their networks and embedded environment.…”
Section: Discussionmentioning
confidence: 99%
“…Their review, which included 22 records, found that macroeconomic interventions, particularly those addressing investments in health and social protection systems, had varied impacts across different countries and populations. The study highlights the effectiveness of cash and unconventional monetary measures, in-kind transfers, social security financing, and targeted measures for specific population groups (Embrett et al, 2021). This evidence is crucial in understanding the diverse strategies that can be employed in the U.S. context for postpandemic economic recovery.…”
Section: Defining the Scope: Recovery Strategies And Policy Intervent...mentioning
confidence: 97%
“…Our study makes an important contribution to the literature by providing a detailed, systematic, and reproducible search that focuses specifically on the available evidence of the role that social protection and taxation policies-namely, those responding to crises-have played within LMICs over the last 20 years. Conversely, existing literature reviews focus solely on the role of social protection in mitigating the effects of the COVID-19 pandemic (Abdoul-Azize and el Gamil 2021; Mawani et al 2021), the effects of COVID-19 on children (Aurino and Giunti 2022), and on macroeconomic policies in general before the pandemic (Embrett et al 2021). Other broad literature reviews have also not been as clear or transparent in documenting their search criteria (Oxford Policy Management 2017).…”
Section: Introductionmentioning
confidence: 99%